2021
DOI: 10.1017/spq.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

Marginalization and Mobilization: The Roots of Female Legislators’ Collaborative Advantage in the States

Abstract: Scholars have argued that female legislators are more prone to collaborate than their male counterparts. Though collaboration may be more or less evident in particular situations, we seek to more clearly establish the mechanism behind women’s collaborative activity using the framework of marginalization. In this paper, we use cosponsorship data from 74 state legislative chambers from 2011–2014 to analyze collaborative patterns and mobilizing institutions. We find female legislators are more collaborative than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…These countries are a good selection because, first, they include varying levels of descriptive representation by women in politics: within the OECD, Ireland has notoriously low levels of women in parliament (never above 20%), while Sweden is one of the Western countries closest to parity, currently at around 44% of women MPs. This variation is important as previous research has shown that women in parliament are more likely to cosponsor legislation with other women, specifically when there are few women elected (Barnes 2016; Holman, Mahoney, and Hurler 2022; Swift and VanderMolen 2021). Therefore, we would expect speeches to be more distinct in situations in which few women are in parliament.…”
Section: Empirical Strategymentioning
confidence: 99%
“…These countries are a good selection because, first, they include varying levels of descriptive representation by women in politics: within the OECD, Ireland has notoriously low levels of women in parliament (never above 20%), while Sweden is one of the Western countries closest to parity, currently at around 44% of women MPs. This variation is important as previous research has shown that women in parliament are more likely to cosponsor legislation with other women, specifically when there are few women elected (Barnes 2016; Holman, Mahoney, and Hurler 2022; Swift and VanderMolen 2021). Therefore, we would expect speeches to be more distinct in situations in which few women are in parliament.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Another context that may condition women’s capacity to impact policy outputs is the gender composition of the board. Evidence suggests that women excel at collaborative policymaking (Bratton and Rouse 2011; Swift and Vandermolen 2021). Women policymakers are also adept at utilizing networking opportunities to help them overcome gendered institutions and other biases (Holman and Mahoney 2018; Wojcik and Mullenax 2017; Holman, Mahoney and Hurler 2021).…”
Section: The Conditions and Constraints Of Women’s Discretionmentioning
confidence: 99%
“…Access to leadership positions in state legislatures is important because formal and informal powers allow leaders to influence the behavior of their colleagues in pursuit of their goals—whether that be to adopt a particular policy, achieve an institutional objective, or unite as a party (Swift and VanderMolen 2021). Among these powers are committee appointments, agenda setting, staff resources, and campaign resources (Jewell and Whicker 1994).…”
Section: Women’s Marginalization and Electoral Vulnerabilitymentioning
confidence: 99%
“…We argue that cosponsorship, which is generally associated with higher bill quality and increased bill success (Barnes 2016; Eatough, Preece, and Barber 2020; Gutmann and Thompson 2012; Kirkland 2011), represents a key measure of women’s collaboration with each other. Because of their exclusion from traditional forms of power in political bodies (Barnes 2016; Jenkins 2007; Senk 2020) and gendered socialization patterns (Schneider and Bos 2019), women legislators’ rate of collaboration is often higher than men’s rate of collaboration (Allen and Childs 2019; Barnes 2016; Bjarnegård 2013; Holman and Mahoney 2018; Swift and VanderMolen 2021). Gender norms incentivize women legislators to work collaboratively not only for bill success but to adhere to social expectations that pressure women to be good team players and share credit for accomplishments (Bauer, Yong, and Krupnikov 2017; Schneider and Bos 2019).…”
Section: Introductionmentioning
confidence: 99%